Lean Service Model to Reduce the Cancellation Rate of Cards in Peruvian Retail Banking - Escudero Arrascue, Maria Fernanda (2023)
The banking services industry has been experiencing, for several years, continuous changes and adaptation in the way they maintain contact with their customers. Financial institutions must submit their processes to changes and adjustments according to the new habits and communication channels maintained by their clients to ensure competitiveness within the industry. This work aims to develop an analysis of the indicators for the lean implementation process in a client attendance Peruvian bank. Maintain a level of service and employ friendly digital tools. An essential part of these considerations is service level management and customer communication. This paper proposes a method that uses various tools such as Lean service, standardization of times in processes, digital marketing plan and Kanban Board, which aims to improve the key indicator of card cancellations of 74% of submitted applications. After implementing the proposed model, this article shows that it is possible to increase the number of account withholdings by a considerable percentage.